Numerical and experimental study of phase-change temperature controller containing graded cellular material fabricated by additive manufacturing. (5th March 2019) - Zhang, Yongcun; Ma, Guangpeng; Wang, Jiayou; Liu, Shutian; Kang, Shuaishuai
Highlights: A three-dimensional numerical analysis is proposed for the integrated phase-change temperature controller fabricated by additive manufacturing. The experiment is carried out to verify the effectiveness of the numerical model. The influences of the graded porosity distribution and packaging structure on the phase change heat transfer process are discussed. Abstract: The improved phase-change temperature control can be obtained by the rational graded cellular design as the thermal conductivity enhancer. 3D printing as an advanced manufacture technique provides a possibility to fabricate the integrated structure with precisely defined complex geometric architecture including the graded cellular structure, which is changing the design profoundly. In this paper, a three-dimensional numerical analysis method is proposed for the integrated phase-change temperature controller simultaneously containing internal graded cellular material and external packaging structure fabricated by additive manufacturing. In the numerical model, the two-equation model considering the phase change process is employed to describe the heat transfer of internal graded cellular material filled with the paraffin wax and the thermal conduction equation is used to calculate the temperature field of the external packaging structure. In addition, the direct couple strategy in the solving process is adopted by setting the same temperature at the interface. The experiment is carried out in order to verify the effectiveness of the numerical model. The measured temperatures under the different heating powers are all in good agreement with ones by the numerical model, which indicate that the experimental and numerical results are reliable. The parameter analysis shows that the distribution of porosity in the cellular material and the wall thickness of packaging structure have a significant influence on phase change process, and the heat transfer performance of thermal controller should be improved by the collaborative design of the internal cellular material and external packaging structure.